2019
DOI: 10.18203/2320-6012.ijrms20191664
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of skin tumours

Abstract: Background: Skin cancers are relatively uncommon malignancies worldwide, but the incidence of skin cancers has progressively increased over the last few decades. The distinction between benign and malignant neoplasm are more difficult to define when they appear in skin than when found elsewhere and histopathological examination is frequently required to establish a definitive diagnosis. Diagnosis of any skin tumours can be done by correlating clinical features and histological features. The aim and objective w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 3 publications
10
14
2
Order By: Relevance
“…In our study, maximum number of skin tumors, both benign and malignant were seen in the head, face and neck region which is comparable with the studies from Karki et al, Shrivastava et al and Narhire et al 10,[13][14] Head, face and neck are the sun exposed areas and of cosmetic concern to the patients, which might explain the high frequency of tumors.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, maximum number of skin tumors, both benign and malignant were seen in the head, face and neck region which is comparable with the studies from Karki et al, Shrivastava et al and Narhire et al 10,[13][14] Head, face and neck are the sun exposed areas and of cosmetic concern to the patients, which might explain the high frequency of tumors.…”
Section: Discussionsupporting
confidence: 92%
“…10,12 Studies from India also showed higher number of benign tumors. 9,[13][14] In our study, the majority of skin tumors were keratinocytic 35.2%, followed by soft tissue tumors 31.2%, melanocytic tumors 16.8% and appendageal tumors 9.6%. Keratinocytic tumors have been observed to be the commonest skin tumors in Nepal in studies done by Sherpa and KC and Thapa et al also.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Cutaneous adnexal tumors usually present with asymptomatic papules or nodules. Although they give the clinicians a clue due to their anatomical location, number and distribution, histopathological examination is the gold standard in diagnosis [5]. Yet, due to the presence of large histomorphological patterns in the histopathological examination, it may be confusing to use many different terms together when describing the same tumor [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although they give the clinicians a clue due to their anatomical location, number and distribution, histopathological examination is the gold standard in diagnosis [5]. Yet, due to the presence of large histomorphological patterns in the histopathological examination, it may be confusing to use many different terms together when describing the same tumor [5]. Different diagnoses may be made histopathologically outside of what is written in clinical prediagnoses due to the presenting clinical and histopathological similarities.…”
Section: Introductionmentioning
confidence: 99%